2022
DOI: 10.1145/3485732
|View full text |Cite
|
Sign up to set email alerts
|

Are They Learning or Playing? Moderator Conditions of Gamification’s Success in Programming Classrooms

Abstract: Students face several difficulties in introductory programming courses (CS1), often leading to high dropout rates, student demotivation, and lack of interest. The literature has indicated that the adequate use of gamification might improve learning in several domains, including CS1. However, the understanding of which (and how) factors influence gamification’s success, especially for CS1 education, is lacking. Thus, there is a clear need to shed light on pre-determinants of gamification’s impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 86 publications
1
17
1
4
Order By: Relevance
“…Recent studies suggested that the MSP approach can help students feel less stressed, more confident, and make them achieve higher levels of satisfaction and greater performance [5,3]. Indeed, based on recent MSP results, an increasing number of computer science departments have adopted this approach in CS1 classes [5,44,15,28,16,48].…”
Section: Many Small Programs Approachmentioning
confidence: 99%
“…Recent studies suggested that the MSP approach can help students feel less stressed, more confident, and make them achieve higher levels of satisfaction and greater performance [5,3]. Indeed, based on recent MSP results, an increasing number of computer science departments have adopted this approach in CS1 classes [5,44,15,28,16,48].…”
Section: Many Small Programs Approachmentioning
confidence: 99%
“…To achieve that goal, gamification must be well-designed, or it can be ineffective or lead to performance loss and indifference, among other negative effects [Toda et al 2018b]. That happens because poor designs can, for instance, decrease motivation and, consequently, lead to negative behavioral effects, such as careless completion of educational activities [Landers et al 2018, Rodrigues et al 2022. Using design frameworks and personalization strategies, among other alternatives, can maximize gamification effectiveness [Toda et al 2018a, Rodrigues et al 2020].…”
Section: Background and Related Workmentioning
confidence: 99%
“…O estudo foi realizado com 101 estudantes e apesar de ter sido identificado um aumento do desempenho dos alunos no ambiente de aprendizado online, não se observou diferenc ¸a significativa entre os tipos de jogadores nos resultados de aprendizado dos alunos. Rodrigues et al (2022) realizaram um estudo onde elementos de gamificac ¸ão foram adicionados a uma ferramenta de juiz online. Uma ferramenta de juiz online tem foco em competic ¸ão e resoluc ¸ão de desafios de programac ¸ão.…”
Section: Trabalhos Relacionadosunclassified
“…"Code" representa a prática contínua de codificac ¸ão. Ao expor o aluno a prática constante, o aluno se sente cada vez mais seguro ao programar [Rodrigues et al 2022]. Além disso, o modelo utiliza ferramentas que permitem o aluno executar e avaliar o código implementado antes de submetê-lo para a avaliac ¸ão pelo instrutor.…”
Section: Visão Geralunclassified
See 1 more Smart Citation